Bacillus subtilis as a vegetable growth promoter inoculant in soybean - Chagas Junior, Aloisio Freitas (2022)
The use of Bacillus subtilis as an inoculant can promote plant growth through several mechanisms. Thus, the objective of this work was to evaluate the efficiency of Bacillus subtilis as a soybean plant growth promoter inoculant. Seven isolates of B. subtilis (Bs01; Bs02; Bs03; Bs04; Bs05; Bs06 and Bs10) were evaluated for their ability to solubilize phosphate and synthesis of indole acetic acid, in vitro, and in the production of biomass of soybean plants in vegetation House. All isolates were able to solubilize phosphate and produce indole acetic acid (IAA). For the evaluated characteristic of shoot and root biomass, the treatment with inoculation of the Bs10 strain was superior (p<0.05) to the others, in the first evaluation at 30 days after sowing (DAS) and at 52 DAS the treatments with the inoculations with strains Bs05, Bs06 and Bs10 were significantly higher (p<0.05). The B. subtilis strains showed efficiency in the variables analyzed in relation to the control without inoculation. The efficiency of the use of B. subtilis in plant growth is related to the biological characteristics of this microorganism, which expresses facilities for maintaining its viability in bioformulates and, therefore, its potential to promote plant growth.